Efecto antimicótico del extracto acuoso y etanólico de Plantago major (Llantén) frente a Candida albicans - Tineo Cueva, Mariasbel; Román Damián, César Eduardo (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
Objetivo: Determinar el efecto antifúngico del extracto acuoso y etanólico de Plantago major (llantén) frente a Candida albicans. Metodología: Inductiva, transversal, prospectiva con diseño experimental, los extractos acuoso y etanólico se trabajaron al 50% y 100%. Resultados: Los halos de inhibición para el extracto acuoso de Plantago major al 50% fue de 7,40 + 0,28mm y de 11,55 + 0,36mm para el 100%, así mismo, para el extracto etanólico de Plantago major al 50% fue de 12,66 + 0,25mm y de 14,91 + 0,39mm para el 100%; el control negativo (etanol) de 6,07mm + 0,24 y el control positivo (nistatina) de 23,94mm + 0,29. Conclusiones: Los extractos acuoso y etanólico de Plantago major (llantén) presentaron efecto antifúngico frente a Candida albicans a las concentraciones del 100% y 50%

Objective: To determine the antifungal effect of aqueous and ethanolic extracts of Plantago major (plantain) against Candida albicans. Methodology: Inductive, cross-sectional, prospective with experimental design, the aqueous and ethanolic extracts were worked at 50% and 100%. Results: The inhibition halos for the aqueous extract of Plantago major at 50% were 7.40 + 0.28 mm and 11.55 + 0.36 mm for 100%, likewise, for the ethanolic extract of Plantago major at 50% were 12.66 + 0.25 mm and 14.91 + 0.39 mm for 100%; the negative control (ethanol) was 6.07 mm + 0.24 and the positive control (nystatin) was 23.94 mm + 0.29. Conclusions: The aqueous and ethanolic extracts of Plantago major (plantain) showed antifungal effect against Candida albicans at the concentrations of 100% and 50%
Antifungal effect of the aqueous and ethanolic extract of Plantago major (Plantain) against Candida albicans
Keywords: Extracto acuoso; Etanólico; Plantago major; Llantén; Candida albicans; Antifúngico; https://purl.org/pe-repo/ocde/ford#3.01.05